2010
DOI: 10.1177/1934578x1000500224
|View full text |Cite
|
Sign up to set email alerts
|

Composition at Different Development Stages of the Essential Oil of Four Achillea Species Grown in Iran

Abstract: Cineole (27-41%) was the main compound in the oils from A. millefolium and A. biebersteinii. These two species reached the highest amount of volatile compounds at the full blooming stage. α-Thujone was the main compound in A. nobilis oil (25-64%). Fully blooming plants of this species also had a high proportion of artemisia ketone (up to 40%) in the oil. The main oil compounds of A. eriophora were camphor (about 35%) and 1,8-cineol (about 30%). This species produces only a small number of flower heads and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Considering the results of GC/MS analysis performed for the studied species, piperitone (19.79 %), camphor (77.19 %), α ‐terpinene (22.28 %), eucalyptol (28.28 %), artemisia ketone (31.90 %), eucalyptol (22.89 %), endo ‐borneol (30.07 %), β ‐eudesmol (22.46 %), camphor (38.96 %), eucalyptol (37.44 %), camphor (16.55 %), verbenol (27.98 %), endo ‐borneol (73.05 %), camphor (18.87(%), β ‐eudesmol (29.17 %) and β ‐eudesmol (39.59 %) were found to be major components. The results of the study are in line with the literature . It can be said that the essential oil contents of Achillea species are affected by factors such as collection period, soil structure and climatic conditions.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Considering the results of GC/MS analysis performed for the studied species, piperitone (19.79 %), camphor (77.19 %), α ‐terpinene (22.28 %), eucalyptol (28.28 %), artemisia ketone (31.90 %), eucalyptol (22.89 %), endo ‐borneol (30.07 %), β ‐eudesmol (22.46 %), camphor (38.96 %), eucalyptol (37.44 %), camphor (16.55 %), verbenol (27.98 %), endo ‐borneol (73.05 %), camphor (18.87(%), β ‐eudesmol (29.17 %) and β ‐eudesmol (39.59 %) were found to be major components. The results of the study are in line with the literature . It can be said that the essential oil contents of Achillea species are affected by factors such as collection period, soil structure and climatic conditions.…”
Section: Resultssupporting
confidence: 87%
“…In addition, in the study of Azizi et al., p ‐cymene and eucalyptol contents of this species have been found to change seasonally. Moreover, p ‐cymene (18.6 %), 1,8‐cineole (16.5 %) and camphor (11.7 %) were identified as major constituents in a study conducted on samples of the same species collected from close locality and at different years.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Achillea millefolium was studied by GC [26][27][28][29][30][31][32], therewith this herb was a component of an elixir [26]. Orav et al [28] compared the compositions of the essential oils of Achillea millefolium collected in different European countries.…”
Section: Herbal Drug Raw Materials and Herbal Mixturesmentioning
confidence: 99%
“…The chemical compositions of A. biebersteinii essential oils reported from different geographic regions [15][16][17][18][19][20][21][22][23][24][25][26] are summarized in Table 3. Monoterpenes, with quantitative and qualitative differences, represented the largest group in these previous reports [15][16][17][18][19][20][21][22][23][24][25][26], an exception being one sample from Iran, which was found to be rich in the sesquiterpene, spathulenol. Rahimmalek et al [21] reported a high level of spathulenol and a high essential oil yield, which might be due to a soil characterized by an accumulation of CaCO 3 .…”
mentioning
confidence: 99%